Perinatal exposure to a dietary pesticide cocktail does not increase susceptibility to high-fat diet-induced metabolic perturbations at adulthood but modifies urinary and fecal metabolic fingerprints in C57Bl6/J mice. (November 2020) - Smith, Lorraine; Klément, Wendy; Dopavogui, Léonie; de Bock, Frédéric; Lasserre, Frédéric; Barretto, Sharon; Lukowicz, Céline; Fougerat, Anne; Polizzi, Arnaud; Schaal, Benoist; Patris, Bruno; Denis, Colette; et al.
Abstract: Background: We recently demonstrated that chronic dietary exposure to a mixture of pesticides at low-doses induced sexually dimorphic obesogenic and diabetogenic effects in adult mice. Perinatal pesticide exposure may also be a factor in metabolic disease etiology. However, the long-term consequences of perinatal pesticide exposure remain controversial and largely unexplored. Objectives: Here we assessed how perinatal exposure to the same low-dose pesticide cocktail impacted metabolic homeostasis in adult mice. Methods: Six pesticides (boscalid, captan, chlopyrifos, thiachloprid, thiophanate, and ziram) were incorporated in food pellets. During the gestation and lactation periods, female (F0) mice were fed either a pesticide-free or a pesticide-enriched diet at doses exposing them to the tolerable daily intake (TDI) level for each compound, using a 1:1 body weight scaling from humans to mice. All male and female offsprings (F1) were then fed the pesticide-free diet until 18 weeks of age, followed by challenge with a pesticide-free high-fat diet (HFD) for 6 weeks. Metabolic parameters, including body weight, food and water consumption, glucose tolerance, and urinary and fecal metabolomes, were assessed over time. At the end of the experiment, we evaluated energetic metabolism and microbiota activity using biochemical assays, gene expression profiling, and 1 H NMR-based metabolomics in the liver, urine, and feces. Results: Perinatal pesticide exposure did not affect body weight or energy homeostasis in 6- and 14-week-old mice. As expected, HFD increased body weight and induced metabolic disorders as compared to a low-fat diet. However, HFD-induced metabolic perturbations were similar between mice with and without perinatal pesticide exposure. Interestingly, perinatal pesticide exposure induced time-specific and sex-specific alterations in the urinary and fecal metabolomes of adult mice, suggesting long-lasting changes in gut microbiota. Conclusions: Perinatal pesticide exposure induced sustained sexually dimorphic perturbations of the urinary and fecal metabolic fingerprints, but did not significantly influence the development of HFD-induced metabolic diseases.